2018
DOI: 10.18488/journal.aefr.2018.86.832.842
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles toward Adopting Electronic Government in an Emerging Economy: Evidence from Kuwait

Abstract: Article HistoryThe current study provides assessment to the current system of e-government in Kuwait. It also identifies possible obstacles towards promoting effective e-government and what should be done to alleviate these obstacles. A questionnaire survey has been used to achieve the aim of the study. During January and April 2017 the questionnaire was distributed to 275 public sector employees. Of which 200 returned completed resulting in 72% usable response rate. Descriptive statistics was performed togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Facilitating conditions such as organisational factors become priority areas to test and examine in this research based on the explanation of robustness of the UTAUT model revealed by Rodrigues et al (2016), Dahi and Ezziane, (2015), Rabaa’i (2017) and AL-Mutairi et al (2018). The UTAUT combines the main features proposed by eight technology acceptance models such as reasoned action theory (Davis et al , 1989) , TAM (Davis, 1989), model of motivation (Davis et al , 1992), planned behavioural theory (Ajzen, 1991), combination of TAM and theory of planned behaviour (Taylor and Todd, 1995), personal computer utilisation (Thompson et al , 1991), diffusion of innovation (Rogers, 1995) and theory of social cognition (Compeau and Higgins, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Facilitating conditions such as organisational factors become priority areas to test and examine in this research based on the explanation of robustness of the UTAUT model revealed by Rodrigues et al (2016), Dahi and Ezziane, (2015), Rabaa’i (2017) and AL-Mutairi et al (2018). The UTAUT combines the main features proposed by eight technology acceptance models such as reasoned action theory (Davis et al , 1989) , TAM (Davis, 1989), model of motivation (Davis et al , 1992), planned behavioural theory (Ajzen, 1991), combination of TAM and theory of planned behaviour (Taylor and Todd, 1995), personal computer utilisation (Thompson et al , 1991), diffusion of innovation (Rogers, 1995) and theory of social cognition (Compeau and Higgins, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%